Programa Nacional de Fortalecimento da Agricultura Familiar - impactos na região do Corede Missões/RS: uma análise a partir da percepção dos beneficiários - Lenz, Solei Rejane (2020)
The family farming plays an important economic and social role, with the production of food for the population, and as an instrument for generating employment and income in rural areas. The National Program for Strengthening Family Agriculture aims to promote the sustainable development of the rural segment made up of family farmers, in order to provide them with an increase in productive capacity, job creation and income improvement. In this context, the study aimed to identify how family farmers in the region covered by COREDE Missões/RS manage Pronaf resources, what are the productive impacts, and what is the perception of financial well-being and improvement of the beneficiaries' quality of life. The data used comes from the application of questionnaires with 263 beneficiaries of the Program distributed in 25 municipalities in the state of Rio Grande do Sul. The analysis of the data occurred through descriptive statistics and cluster analysis. As main results, the Program's contribution to the increase of the productive capacity is pointed out, through investments for the acquisition of inputs, machines and equipment and access to new technologies. As for the quality of life, there are very satisfactory perceptions in the dimensions of health, housing and personal relationships, with some aspects of the environmental domain that need to be improved. In addition, the level of financial well-being of most families is intermediate. Of the three formed, the one with the fewest beneficiaries is composed of those with the worst perceptions clusters of quality of life and financial well-being, and they spend the same or more than they earn, have a low educational level and a lower degree income. Whereas, in the cluster with better quality of life, there is a higher percentage of members with higher levels of income, education, more access to credit cards and greater satisfaction with the financial situation. It is concluded that Pronaf fulfills the objective of promoting the development of family farming, however, there are still some difficulties in the region regarding the distancing of producers from the large food marketing networks.